2014
DOI: 10.1088/1741-2560/12/1/016010
|View full text |Cite
|
Sign up to set email alerts
|

Chemical stimulation of rat retinal neurons: feasibility of an epiretinal neurotransmitter-based prosthesis

Abstract: We provide strong support for the feasibility of an epiretinal neurotransmitter-based retinal prosthesis. Our findings suggest that chemical stimulation of RGCs is a viable alternative to electrical stimulation and could offer distinct advantages such as the selective stimulation of RGC somata.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 77 publications
2
44
0
Order By: Relevance
“…PSTHs were further analyzed by extracting the temporal characteristics of spike rate responses including the time width and response latency. The time width of responses was calculated as the width at half maximum amplitude while the response latency was determined to be the first time point of the width 14 . These analyses were performed on RGC response data corresponding to both chemical and visual stimulation to facilitate comparisons of the spike rate temporal characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PSTHs were further analyzed by extracting the temporal characteristics of spike rate responses including the time width and response latency. The time width of responses was calculated as the width at half maximum amplitude while the response latency was determined to be the first time point of the width 14 . These analyses were performed on RGC response data corresponding to both chemical and visual stimulation to facilitate comparisons of the spike rate temporal characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…Both the patterned responses of RGCs and spatial localization of glutamate stimulation were investigated by mapping the locations of glutamate-responsive RGCs exhibiting somal spike shapes using the vectors separating electrodes recording responsive units from the glutamate injection sites. Units exhibiting somal, as opposed to axonal, spike shapes were specifically utilized since they are more closely colocalized with glutamate receptors (for details see Inayat et al 14 ), the intended primary targets of this neurotransmitter stimulation. For each stimulation pattern, these vectors were assembled into a 2D histogram via spatial binning to represent the approximate locations of electrodes where responsive RGCs were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A neurotransmitter chemical, particularly glutamate, the main agent of intercellular communication in the normal retina, has long been suggested as a more effective stimulus agent than electrical current for a retinal prosthesis, though very few studies have explored the feasibility of retinal stimulation with neurotransmitters15161718. Two studies1718 that have demonstrated the feasibility of glutamate stimulation of in-vitro preparations of whole retinas focused on direct stimulation of RGCs from the epiretinal side.…”
mentioning
confidence: 99%
“…Two studies1718 that have demonstrated the feasibility of glutamate stimulation of in-vitro preparations of whole retinas focused on direct stimulation of RGCs from the epiretinal side. These studies showed glutamate to be effective and advantageous over electrical current in stimulating RGCs, but since they bypassed INL neurons, they did not take advantage of the intrinsic visual processing capability of INL circuitry.…”
mentioning
confidence: 99%